Revolutionizing Indonesia’s Administrative Court: A Bold Push for Fairness and Proportionality - Rahman, Nazla Arliva; Damayanti, Ratih; Rajib, Rayi Kharisma (Indonesian State Law Review, 2024)
Indonesia's administrative justice system is at a critical juncture, facing challenges of inefficiency, inconsistency, and limited access to fair legal recourse. This research examines the urgent need for a transformative approach in establishing an Indonesian Administrative Court grounded in the principles of fairness and proportionality. Despite progress in administrative reform, the current system often falls short of delivering just outcomes for citizens, leaving many marginalized and without proper redress. The novel contribution of this study lies in its comprehensive framework for integrating these foundational principles into the court’s design and practice. By analyzing both international best practices and local judicial traditions, the research proposes a set of reforms that would enhance the accessibility, transparency, and responsiveness of the administrative judiciary. The principle of fairness emphasizes equal treatment and impartial decision-making, while proportionality ensures that legal outcomes align with the scale of the issues at hand. Through an in-depth case study of administrative court decisions, this work identifies critical gaps where these principles can be meaningfully implemented. The urgency of these reforms is underscored by the growing demand for public accountability and citizen trust in the judiciary, which is essential for Indonesia’s democratic stability. By offering practical solutions and a conceptual shift, this research provides a timely contribution to the ongoing discourse on judicial reform in Indonesia, with the potential to reshape the administrative court system into a more equitable and effective institution for all citizens.